A Case Series On Fatal Self-Inflicted Cut Throat Injuries Reported At An Autopsy Centre Of An Apex Hospital Of West-Bengal, India - Saren, Biswanath; Bag, Kanad; Das, Indrani (Journal of Forensic Medicine and Toxicology, 2026)
Of the various methods adopted for committing suicide, suicide by inflicting cut throat injuries are painful, hence rare.  Fatal cut throat injuries are mostly homicidal. In cases of fatal cut throat injuries, findings noted over neck and body  does not conclusively determine the manner of death. Features classically present in suicidal cut-throat injuries may  be present in homicides and vice-versa. Thus, they may be misleading or confusing. In such cases the findings of the  Postmortem examination alone are insufficient to opine whether the death is suicidal or homicidal. Hence, along with  the postmortem report of the victim, reports of police inquest, on the circumstances, mental state and relevant history  of the victim are important considerations. Corroborating the wound with the recovered weapon, report of the Forensic  Science Laboratory on the place of occurrence and on the materials preserved during Autopsy should be incorporated  to form a conclusive opinion on the cause and manner of death in cases of fatal cut-throat injuries. A series of three such  rare cases, has been illustrated. Diverse aspects of medicolegal investigation that ultimately led to forming a conclusive  opinion on the manner of death has been described. This series of cut-throat injuries demonstrates the importance of  inclusion of all aspects of forensic investigation to conclude on the suicidal manner of death.
Keywords: fatal; self-inflicted; cut-throat injuries